A novel experimental study on the fabrication and biological characteristics of canine bone marrow mesenchymal stem cells sheet using vitamin C. Issue 1 (14th January 2015) - Guo, Peng; Zeng, Jing‐jing; Zhou, Nuo
Summary The aim of this study was to fabricate canine bone marrow mesenchymal stem cell sheet through the use of vitamin C, to identify the biological characteristics of the resulting cell sheets, and to reveal the potential mechanism of cell‐sheet promotion by vitamin C. This study used vitamin C to induce bone marrow mesenchymal stem cells to proliferate. The resulting cells secreted large amounts of collagen, thereby shortening the construction time of the cell‐sheet layer. In addition to these aims, we identified biological microcharacteristics of the cell sheet through histological observation, transmission electron microscopy, real‐time PCR detection, immunohistochemical detection, and osteogenesis‐induction experiments on the cell sheet. We were able to stably and rapidly construct bone marrow mesenchymal stem cell sheet, effectively harvest it, and transfer the seed cells for tissue engineering. This study indicates that the use of vitamin C for harvesting mesenchymal stem cell sheets from bone marrow may provide an easy and practical approach for bone tissue regeneration. SCANNING 37:42–48, 2015. © 2015 Wiley Periodicals, Inc.